Expanding Boundaries Borders, Mobilities and the Future of Europe-Africa Relations (Taylor & Francis, 2020)
This book challenges the common European notions about African migration to Europe and offers a holistic understanding of the current situation in Africa. It advocates a need to rethink Africa-Europe relations and view migration and borders as a resource rather than sources of a crisis.
English
Keywords: Human geography; migration, african migration, borders, boundaries, population geography, political geography, external migration, border studies, conflict and security studies